Abuso sexual contra criança e adolescente : análise de inquéritos - Santos, Elenice Martins da Silva (2019)
Introduction: Sexual abuse against children and adolescents has been a serious public health problem and can cause several physical and psychological consequences for victims, in addition to consuming financial resources that could be invested in key sectors such as health and education. In this scenario, the importance of the outcome of cases of child and youth sexual abuse in the investigation phase is highlighted, considering that the use of legal devices can break this cycle of violence that directly affects the physical and emotional health of the victims and family. Objective: The present study had as main objective to analyze police investigations of sexual abuse against children and adolescents up to the age of 18, registered at the Police Department for the Defense of the Rights of Children and Adolescents (DEDDICA) in Cuiabá, in 2016. Methodology : This is a quantitative, descriptive and cross-sectional study, in which the data were processed electronically using the computer program Epi-Info, version 7.2. Descriptive statistics were performed, using simple and bivariate analyzes. For the bivariate analyzes, the Chi-Square test was used, considering the results in which the p (p) value was equal to or less than 0.05 to be statistically significant. Results: 137 were analyzed, with 156 victims, the majority of whom were female (92.31%) and the age group between 10 to 14 years old was the most affected (38.89%), most of whom were from low-income families, 1 to 2 minimum wages (34.62%), with four members or more (57.06%) and the majority of victims lived only with the mother (30.77%). Most of the aggressors were male (92.95%), over 40 years old (36.54%), who had a marital relationship, married or living together (55.77%), with low income (31, 41%) from 1 to 2 minimum wages, in contrast to a minority that received more than 5 wages (2.56%) and had an informal job (21.15%), mostly self-declared Catholics (23.71%) and evangelicals (21.79%), had completed high school (19.87%), were people known to the victims and / or their families (94.23%), and of these, the stepfather alone accounted for most of the abuses (21.15%), alcoholism was the most visible variable (12.18%), followed by the combination of two or more risk factors (10.26%). The mother was the main whistleblower (51.92%), and there was no complaint made by health professionals. Abuses occurred mainly during the day (41.67%), with emphasis on repeated abuses, that is, more than four episodes (42.31%), about the ambience most of the victims slept in the same room as the aggressor (26.67%). As for the acts practiced in the abuse, the majority occurred through libidinous acts (79,48%), typified as Rape of Vulnerable in 149 cases, with physical contact (90.38%), most of the victims (110) confirmed having suffered sexual abuse, while the majority of aggressors (64.55%) denied the facts, there was a significant difference between the time of abuse and how often it occurred, it was noted that the longer the time of abuse, the greater the frequency of episodes (p = 0.00) and between the place where the abuse occurred and the parents' marital status (p = 0.00), the majority of abuses occurred in the domestic environment (80.14%). As for the outcome, just over half had been completed with authorship (58.97%). Of the completed surveys (109), regardless of whether or not with authorship, most (24.77%) took from 1 to 2 years to complete, while only (21.10%) were completed meeting the legal deadline of 30 days for suspect loose. Regarding the inquiries in progress (46), most (56.52%) had been in progress for more than 02 years, the interrogation was the biggest pending (69.84%). When crossing the number of requested extensions with the number of diligences carried out, after granting a new term, it was noticed that in several cases (60.94%) no diligence had been carried out. This proportion was higher in surveys in which there were 4 to 5 requests for extensions (69.23%). Contribution: The study allowed to know the outcome of the investigations in cases of sexual abuse of children and adolescents, as well as the profile of the victims, families and aggressors, as well as the circumstances involved in the occurrence of these crimes, creating a situational diagnosis that, in addition to providing visibility, it can contribute to the formulation of prevention strategies and subsidies for policies to face this phenomenon.